Adrenergic and serotonin receptors affect retinal superoxide generation in diabetic mice: relationship to capillary degeneration and permeability. Issue 5 (9th February 2015) - Du, Yunpeng; Cramer, Megan; Lee, Chieh Allen; Tang, Jie; Muthusamy, Arivalagan; Antonetti, David A.; Jin, Hui; Palczewski, Krzysztof; Kern, Timothy S.
ABSTRACT: Reactive oxygen species play an important role in the pathogenesis of diabetic retinopathy. We studied the role of adrenergic and serotonin receptors in the generation of superoxide by retina and 661W retinal cells in high glucose and of the α1 ‐adrenergic receptor (AR) on vascular lesions of the retinopathy in experimentally diabetic C57Bl/6J mice (and controls) after 2 and 8 months. Compared with 5 mM glucose, incubating cells or retinal explants in 30 mM glucose induced superoxide generation. This response was reduced or ablated by pharmacologic inhibition of the α1 ‐AR (a Gq ‐coupled receptor) or Gs ‐coupled serotonin (5‐HT2, 5‐HT4, 5‐HT6, and 5‐HT7) receptors or by activation of the Gi ‐coupled α2 ‐AR. In elevated glucose, the α1 ‐AR produced superoxide via phospholipase C, inositol triphosphate‐induced Ca 2+ release, and NADPH oxidase, and pharmacologic inhibition of these reactions prevented the superoxide increase. Generation of retinal superoxide, expression of proinflammatory proteins, and degeneration of retinal capillaries in diabetes all were significantly inhibited with daily doxazosin or apocynin (inhibitors of α1 ‐AR and NADPH oxidase, respectively), but increased vascular permeability was not significantly affected. Adrenergic receptors, and perhaps other GPCRs, represent novel targets for inhibiting the development of important features of diabetic retinopathy.—Du, Y., Cramer, M., Lee, C. A., Tang, J., Muthusamy, A., Antonetti, D. A., Jin, H., Palczewski, K., Kern, T. S. Adrenergic and serotonin receptors affect retinal superoxide generation in diabetic mice: relationship to capillary degeneration and permeability. FASEB J. 29, 2194‐2204 (2015). www.fasebj.org